Organizacyjne aspekty controllingu finansowego w zakładach ubezpieczeń działu II - Chmielowiec-Lewczuk, Magdalena (The Aspects of Financial Controlling Organization in Nonlife Insurance Companies, 2006)
The aim of this paper is to present problems with organizing of controlling in nonlife insurance companies. These problems concern acting and qualifications of members of this department. The essence of this problem is how to transfer some of the cases of controlling application from other companies to insurance companies. There are four variants of placing controlling department, which mean different range of activity, responsibility and relations with other departments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 272-280